2003
DOI: 10.1160/th03-02-0097
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of platelet activation in several different anticoagulants by the Advia 120 Hematology System, fluorescence flow cytometry, and electron microscopy

Abstract: In vivo platelet activation results are often confounded by activation induced in vitro during the preparative procedures. We measured ex vivo (basal) and in vitro (thrombin-induced) platelet activation in sodium citrate, ethylenediaminetetraacetic acid (EDTA), and Citrate Theophylline Dipyridamole Adenosine (CTAD) whole blood specimens. Determinations were made by measurements of platelet density (mean platelet component: MPC concentration) on the Advia 120 Hematology System. The MPC has been previously shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…In this study and others, MPC has been shown to be increased in inactivated platelets and decreased in activated platelets (20,22). The measurement of MPC does not require specimen preparation, platelet activation specific receptors, or activation-specific receptor labels.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…In this study and others, MPC has been shown to be increased in inactivated platelets and decreased in activated platelets (20,22). The measurement of MPC does not require specimen preparation, platelet activation specific receptors, or activation-specific receptor labels.…”
Section: Discussionsupporting
confidence: 60%
“…The patients were characterized based on the combination of the baseline platelet activation parameters, MPC and CD62 expression, and the response to the anti-platelet therapy. For our population, we have already reported a normal MPC value, 27.9 ± 0.9 (22). In a larger set of data (n = 51), the MPC in normal healthy donors was 28.1 ± 1.0 g/dL (data not published).…”
Section: Platelet Activation Status In Patients Receiving Clopidogrelmentioning
confidence: 77%
See 3 more Smart Citations